Analisis pengaruh Corporate Governance terhadap aktivitas Tax Avoidance dengan Siklus Hidup Perusahaan sebagai Variabel Moderasi - Nathania Allisya Krisira; Valerie Angela Halim; Yulius Jogi (Business Accounting Review, 2020)
Company always makes efforts to maximize its profits, including tax avoidance that's usually done by the management to increase profits for the company. To minimize the occurrence of tax avoidance, companies have to implement good corporate governance in their company. In every life cycle that company goes through, it also influences the tax avoidance actions that can be taken to maintain the company. This study aims to examine the relationship of corporate governance to tax avoidance that is moderated by the firm's life cycle. The total sample studied with a purposive sampling is 24 companies in the consumption industry sector listed on the Indonesia Stock Exchange for the 2015-2019 period. Data is analysed with a multiple linear regression that is then processed by using GRETL. Based on the results of the analysis, the components of corporate governance have no effect on tax avoidance, but the existence of a life cycle phase can affect independent commissioners and institutional ownership with tax avoidance.